(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Results of three years studies on an integrated decision system for the control of Codling moth, Cydia pomonella L., are reported. The studies have been conducted from 1990 to 1992 in nine apple orchards in the Trentino area (Italy). Four methods are used to provide warnings: pheromone trapping, collection of trap bands, inspection of fruits for signs of damage and day-degrees. Cumulative captures of males are related to temperature sums over the developmental threshold. In May pheromone traps are started and the cumulative catch at 250 day-degrees is used to predict the need to spray the first-generation larvae. A cumulative number of 15 moths per trap should be a safe threshold. The grower can treat when tolerance thresholds are passed, this permitted an average 50% reduction in the number of cover sprays required.